The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.48550/arxiv.1911.02266
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bounded masses in Two Higgs Doublets Models, Spontaneous CP Violation and $\mathbb{Z}_2$ symmetry

Miguel Nebot

Abstract: In Two Higgs Doublet Models shaped by some unbroken symmetry, placing perturbativity requirements on the quartic couplings can imply that the allowed masses of all the fundamental scalars are bounded from above, i.e. there is no decoupling regime for the new scalars. This important property is analysed in detail for the only two viable scenarios, the case with Z 2 symmetry and the case with CP symmetry. It is also noticeable that one exception arises in each case: when the vacuum is assumed to respect the impo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…We can also recover a recent result on the 2HDM [11], because the model is very simple. Consider a 2HDM with a softly broken Z 2 symmetry and complex vevs.…”
Section: A Note On Cp Violationsupporting
confidence: 81%
See 1 more Smart Citation
“…We can also recover a recent result on the 2HDM [11], because the model is very simple. Consider a 2HDM with a softly broken Z 2 symmetry and complex vevs.…”
Section: A Note On Cp Violationsupporting
confidence: 81%
“…Nevertheless, Gunion and Haber [10] have shown that the decoupling limit is recovered by including in the potential a term of dimension two which breaks softly the Z 2 symmetry. Nondecoupling has also been analyzed by Nebot in the 2HDM with spontaneous CP violation, both with and without soft symmetry breaking terms [11]. One further example with 3HDM and a S 3 symmetry has been discussed by Bhattacharyya and Das [12].…”
Section: Introductionmentioning
confidence: 99%
“…as a consequence of tree-level unitarity [49][50][51][52][53][54][55], it follows that the 2HDM with a softly broken Z 2 symmetry and spontaneous CP violation possesses no decoupling limit [56].…”
Section: B a Softly Broken Z 2 Symmetrymentioning
confidence: 99%
“…[7], and in the context of SCPV in the 2HDM in Ref. [6,8]. Nondecoupling effects also occur in models in which the Higgs is a pseudo-Goldstone dilaton [9,10].…”
Section: Higgs Sectormentioning
confidence: 99%